PERBEDAAN KARAKTERISTIK BPR KECIL DAN BPR MENENGAH DI NUSA TENGGARA BARAT - I Nyoman Nugraha Ardana Putra; Dwi Putra Buana Sakti; I Gede Mandra; I Dewa Gede Bisma; GA Sri Oktaryani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
The motivation to the studies was started with the phenomenon shows there was no regulation on classifies small credit bank society (small BPR) and medium credit bank society (medium BPR) like a standard in small medium enterprises (SMES) and it’s also new of OJK regulation. This study aims to classifies credit bank society in the category of small and medium enterprises. Location og this research is on province of West Nusa Tenggara that used a quantitative approach, with research is comparative in clasified size character of credit bank society. The data used is taken from secondary data derived from the reports on financial credit bank society and other publication the credit bank society and Bank of Indonesia as a central bank. Data analysis was the cluster analysis by SPSS to classify the credit bank society. Results show that of a whole of credit bank society in West Nusa Tenggara 29 unit , 23 unit classified as small credit bank society (Small BPR) and 6 unit as Medium credit bank society (Medium BPR). There are the difference between small BPR and medium BPR.